Connectivism as a deterrent pedagogical approach for blind students at Historically Disadvantaged Institutions - Moleke, Heritage; Montle, Malesela Edward (Acitya: Journal of Teaching and Education, 2024)
The educational domain, like other spheres of human endeavour, was impelled to improvise and undergo unforeseen transitions because of covid19. These transitions, among other things, affected teaching and learning processes that had to shift from physical to online mode. Dissimilar to traditional learning approaches such as cognitivism and constructivism which emphasise the cruciality of learning context, connectivism is underpinned by the notion that learning is disseminated through networks using diverse virtual learning platforms. In the case of blind students, these learning platforms require up-to-date technologies for accessibility purposes. The availability of updated technologies is an outstanding matter in most Historically Disadvantaged Institutions (HDI) of higher learning. This disadvantages the affected students in terms of academic progression. Thus, this study aims to divulge the challenges faced by blind students at HDI of higher learning through the Connectivism paradigm. A qualitative descriptive design will undergird the study. Five blind students from HDI will be purposively sampled and interviewed. The findings will be presented and analysed through Qualitative Content Analysis (QCA), and viable recommendations will be made.